Study of Daily Behavior and Home Range of Long-Tailed Monkeys (Macaca fascicularis) in The Use Zone of Satonda Island, Moyo Satonda National Park - Gefire, Baiq Dean; Hadi, Islamul; Syaputra, Maiser (Jurnal Biologi Tropis, 2024)
The long-tailed monkey (Macaca fascicularis) is a type of social primate which in its life is never separated from social interaction or living with others. Social interactions carried out by long-tailed monkeys give rise to various activities between individuals in the population. Environmental conditions influence the behavior of long-tailed monkeys. In their natural habitat, long-tailed monkeys behave as they should, but in disturbed habitats the behavior of long-tailed monkeys can change. This research aims to determine the daily behavior and home range of long-tailed monkeys (Macaca fascicularis). The methods used are the scan sampling method to determine daily behavior and the minimum convex polygon method to determine the home range of long-tailed monkeys (Macaca fascicularis). Daily behavior has varying percentage values ​​with interaction behavior having the highest percentage value, namely 22%, agonistic behavior at 12%, self-care behavior at 12%, movement behavior at 21%, eating behavior at 16%, resting behavior at 15%, and sexual behavior has the lowest value, namely 2%. The home range of the long-tailed monkey (Macaca fascicularis) has an area of 31 ha, the average daily range is 408 meters, the territory area is 1.5 ha, the core area is 0.6 ha, the maximum radius is 802 meters, and night position shift of 45.8 meters.